Resúmenes bibliográficos, vol. 46, no. 2 - Montaldi, Edgardo Raúl (1970)
Se ofrecen reseñas y resúmenes de los siguientes textos: - Kosikowski, Franck. 1966. Cheese and Fermented Milk Foods - Seaman, Alan. 1963. Bacteriology for dairy students. - Steward, F. C. Growth and Organization in Plants - Whitehead, D. C., The role of nitrogen in grassland productivity - Covas, C.; M. Willumson y M. A. O. de Bbañas. Bibliografía sobre cártamo (Carthamus tinctorius LJ - Perspectivas in Phytochemistry. Proseedings of the Phytochemical Society Symposium - Vidal, J. J.; A. Venero, N. Padloc y A. E. Vorano, Los huertos de manzanos de la Escuela “Carlos Spegazzini”.